Multitasking and workplace wellbeing: the roles of job stress and job autonomy - Zheng Wei; Rohayu Abdul-Ghani; Norazila Mat; Rosmah Mat Isa (Frontiers in Psychology)
This cross-sectional study investigated how multitasking associates with workplace wellbeing, emphasizing the mediating role of job stress, and the moderating role of job autonomy. Grounded in the Job Demands-Resources (JD-R) and Conservation of Resources (COR) theories, this research proposed that multitasking negatively associates workplace wellbeing by increasing job stress, and that job autonomy buffers this relationship between multitasking and job stress. Data were collected from 354 employees in the information technology industry in China, with a response rate of 98.33%, ensuring sample adequacy. AMOS 26.0 and SPSS 29.0 were employed in this study to test the hypothesized relationships. Results indicated that job stress partially mediates the relationship between multitasking and workplace wellbeing (VAF = 35.73%). Job autonomy moderates the relationship between multitasking and job stress, weakening the adverse relationship. These findings contribute to the literature by clarifying the dual roles of job stress and job autonomy. Practically, organizations are encouraged to reduce job stressors and enhance autonomy to support employee wellbeing. Future research should explore industry-specific differences and longitudinal dynamics to deepen understanding of multitasking's impact over time.